2012
DOI: 10.1074/jbc.m112.412031
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Endothelial Nitric-oxide Synthase (NOS) S-Glutathionylation by Neuronal NOS

Abstract: Background: Whether neuronal nitric-oxide synthase (nNOS) plays a role in the endothelial NOS (eNOS)-dependent negative inotropic effect of ␤ 3 -adrenergic stimulation remains to be established. Results: nNOS knock-out or inhibition leads to increased superoxide production, eNOS uncoupling, and abrogation of ␤ 3 -adrenergic responses. Conclusion: Disabling nNOS disrupts eNOS function and downstream signaling.Significance: nNOS plays a crucial role in preserving myocardial nitroso-redox balance and coupled eNOS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 46 publications
(89 reference statements)
3
20
0
Order By: Relevance
“…1B–D). Conversely, the eNOS inhibitor L-NAME at dose of 20 mg/kg did not reverse the amelioration conferred by Bay 60-7550 although a higher dose of L-NAME inhibits both eNOS and nNOS based on the previous study (Idigo et al, 2012). Similarly, PKA inhibitor H89 (5 µM, 30 min) did not completely reverse the effect of Bay 60-7550.…”
Section: Resultsmentioning
confidence: 78%
“…1B–D). Conversely, the eNOS inhibitor L-NAME at dose of 20 mg/kg did not reverse the amelioration conferred by Bay 60-7550 although a higher dose of L-NAME inhibits both eNOS and nNOS based on the previous study (Idigo et al, 2012). Similarly, PKA inhibitor H89 (5 µM, 30 min) did not completely reverse the effect of Bay 60-7550.…”
Section: Resultsmentioning
confidence: 78%
“…This was suggested by our studies in the S1412A mutants that inhibited the BRL-induced augmentation of NOS activity, yet still exhibited an antioxidant effect from β3-AR stimulation. Other studies have also suggested that myocardial nNOS can interact specifically with xanthine oxidase reductase (XOR) derived normalO2 [15,29,30], thought to be primarily due to co-localization at the sarcoplasmic reticular membrane. More recently, Idigo et al showed that XOR inhibition restores β3 negative inotropy as well as eNOS coupling in nNOS −/− myocytes [15].…”
Section: Discussionmentioning
confidence: 99%
“…The negative inotropic effect of β3-AR stimulation involves NOS/NO signaling [2,5,10,11], and while it was initially thought to be due to endothelial NOS (eNOS), new data has shown that neuronal NOS (nNOS) also plays a key role [1215]. In mice with nNOS genetically deleted or acutely inhibited, β3-AR-dependent cardiac protection, NO generation, and NOS downstream signaling are lacking in failing mouse myocardium [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the loss or oxidation of BH 4 enhances the glutathionylation of eNOS [42]. Interestingly, nNOS has been shown to regulate the activity of xanthine oxidoreductase, such that the loss of nNOS results in an increase in superoxide, which subsequently leads to an increase in the S-glutathionylation and uncoupling of eNOS [68]. The lack of benefit with BH 4 administration may be due to the continued cycle of NOS uncoupling (due to glutathionylation) and ROS generation, leading to the oxidation of BH 4 .…”
Section: Redox Regulation Of No Signaling and Dysregulation In Carmentioning
confidence: 99%